Unlocking the potential of soil organic carbon in agricultural landscapes in Kenya and Ethiopia - Nyawira, Sylvia Sarah; Girvetz, Evan Hartunian; Abera, Wuletawu (International Center for Tropical Agriculture, 2019)
Soils are a very important component of the global carbon cycle as they contain the largest sink of carbon in the terrestrial biosphere. At the same time, soil organic carbon (SOC) is the basis for soil fertility and the production of food to feed the growing global population. Healthy soils are not only important from an agricultural production point of view, but they also provide a multitude of other benefits that are critical to human well-being.